Theory of Mind in the Pacific: reasoning across cultures - Wassmann, Jürg; Träuble, Birgit; Funke, Joachim (Heidelberg studies in Pacific anthropology, 2013)
HauptbeschreibungThe ascription of desires or beliefs to other people is a milestone of human sociality. It allows us to understand, explain, and predict human behaviour. During the last years, research on children's knowledge about the mental world, better known as theory of mind research, has become a central topic in developmental psychology and the role of cultural impact is subject of various theoretical yet hitherto few empirical accounts. This book is the result of intensive collaboration between anthropologists and psychologists in the field of cross-cultural research on social cognitive development. Five interdisciplinary research teams, coming from the University of Heidelberg, were investigating five Pacific Island societies. All together, they were interested in the question of how and when children in these different cultures come to assign mental states to others. This unique research project combines sound ethnography of different Pacific cultures with thoroughly conducted experimental work, done by developmental psychologists -- it presents a shared, thoughtful analysis of the results and provides deeper insight into current debates on the ontogeny of theory of mind competencies.
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Feldforschung; Ethnopsychologie; Kulturanthropologie; Theory of mind; Pazifischer Raum